Acute pain pathways: protocol for a prospective cohort study. Issue 7 (5th July 2022) - Jeffery, Molly Moore; Ahadpour, Mitra; Allen, Summer; Araojo, Richardae; Bellolio, Fernanda; Chang, Nancy; Ciaccio, Laura; Emanuel, Lindsay; Fillmore, Jonathan; Gilbert, Gregg H; Koussis, Patricia; Lee, Christine; et al.
Abstract : Introduction: Opioid analgesics are often used to treat moderate-to-severe acute non-cancer pain; however, there is little high-quality evidence to guide clinician prescribing. An essential element to developing evidence-based guidelines is a better understanding of pain management and pain control among individuals experiencing acute pain for various common diagnoses. Methods and analysis: This multicentre prospective observational study will recruit 1550 opioid-naïve participants with acute pain seen in diverse clinical settings including primary/urgent care, emergency departments and dental clinics. Participants will be followed for 6 months with the aid of a patient-centred health data aggregating platform that consolidates data from study questionnaires, electronic health record data on healthcare services received, prescription fill data from pharmacies, and activity and sleep data from a Fitbit activity tracker. Participants will be enrolled to represent diverse races and ethnicities and pain conditions, as well as geographical diversity. Data analysis will focus on assessing patients' patterns of pain and opioid analgesic use, along with other pain treatments; associations between patient and condition characteristics and patient-centred outcomes including resolution of pain, satisfaction with care and long-term use of opioid analgesics; and descriptive analyses of patient management of leftover opioids. Ethics and dissemination: This study has received approval from IRBs at each site. Results will be made available to participants, funders, the research community and the public. Trial registration number: NCT04509115 .